School‐age vaccination, school openings and Covid‐19 diffusion. (8th February 2023) - Amodio, Emanuele; Battisti, Michele; Gravina, Antonio Francesco; Lavezzi, Andrea Mario; Maggio, Giuseppe
Abstract: This article investigates the relationship between school openings and Covid‐19 diffusion when school‐age vaccination becomes available. The analysis relies on a unique geo‐referenced high frequency database on age of vaccination, Covid‐19 cases and hospitalization indicators from the Italian region of Sicily. The study focuses on the change of Covid‐19 diffusion after school opening in a homogeneous geographical territory (i.e., with the same control measures and surveillance systems, centrally coordinated by the Regional Government). The identification of causal effects derives from a comparison of the change in cases before and after school opening in the school year 2020/21, when vaccination was not available, and in 2021/22, when the vaccination campaign targeted individuals of age 12–19 and above 19. Results indicate that, while school opening determined an increase in the growth rate of Covid‐19 cases in 2020/2021, this effect has been substantially reduced by school‐age vaccination in 2021/2022. In particular, we find that an increase of approximately 10% in the vaccination rate of school‐age population reduces the growth rate of Covid‐19 cases after school opening by approximately 1%.